ANALYSIS OF PROJECT-BASED LEARNING OUTCOMES ON THE TOPIC OF MIXED SEPARATION OF CLASS X STUDENTS OF SMK NEGERI 4 PALANGKA RAYA - Meileli Florida Anggraini; Abudarin; Abdul Hajranul Fatah (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Learning chemistry requires a strong ability to understand concepts from students, which can be obtained by the motivation of students when learning. One alternative that is seen as capable in increasing motivation and understanding of concepts is that students have critical thinking skills, work actively and collaboratively as a reflection to find out what they have learned and can develop it into new science that is useful for human welfare. In this case, the right learning activity to use is project-based learning or Project Based Learning (PjBL). This type of research is descriptive research, descriptive research is research that seeks to solve problems or answer problems faced now. The results of the study were: (i) The learning ability of grade X students of SMKN-4 Palangka Raya in project-based learning with the help of LKPD on the topic of Mixed Separation amounted to an average of 89.19. Based on the criteria of students' ability to learn that the range of values 81-100 is an understanding with ability level V with the criteria of students' abilities developing very well; (ii) There is a change in the learning interest of grade X students of SMKN-4 Palangka Raya after project-based learning with the help of LKPD on the topic of Mixed Separation. The results of the questionnaire analysis showed that the cumulative percentage of learning interest changed from -31.31% before learning to 98.99% after learning. This shows that students' interest in learning has changed to positive after LKPD-assisted project-based learning on the topic of mixed separation; (iii) The average pretest score is 18.64 and the average postets score is 85. From the pretest and postest data, the N-Gain calculation result is 0.8. Mastery of the concept of grade X students at SMKN-4 Palangka Raya has increased with an N-Gain value of 0.8 with a high category.